Răspunsuri

Cel mai inteligent răspuns!
2014-11-11T11:03:18+02:00
0,(3)= \frac{3}{9}[tex] = [tex] \frac{1}{3}
1,(2)=1 \frac{2}{9} =  \frac{11}{9}
 \frac{1}{3} - \frac{11}{9}x + 0,25 = 2,5 /-0,25
 \frac{1}{3} - \frac{11}{9}x = 2,25
 \frac{11}{9}x = \frac{1}{3}  - 2,25
 \frac{11}{9}x =  \frac{1}{3} - \frac{225}{100}
 \frac{11}{9}x =  \frac{1}{3} -  \frac{3}{4}
 \frac{11}{9}x =  \frac{4}{12} -  \frac{27}{12}
 \frac{11}{9}x = - \frac{23}{12}
x = - \frac{23}{12} :  \frac{9}{4} = - \frac{23}{12} · \frac{4}{9} =- \frac{23}{27}